Produção e bem-estar de ovinos em sistema silvipastoril - van Cleef, Flávia de Oliveira Scarpino [UNESP] (2017)
Silvopastoral systems may contribute to the reduction of the effects caused by climate change in grazing animals. The aim of this study was to evaluate the presence of trees on the behavior, physiological and blood parameters of grazing finishing lambs in Massai grass, as well as the forage mass and quality. Twenty-four crossbred lambs (24±3.3 kg BW) were blocked by initial BW and assigned into three experimental treatments: Unshaded (US)= unshaded Massai grass pasture; Moderate Shade (MS)= Massai grass pasture with eucalyptus trees spaced 12 × 2m; Intense Shade (IS) = Massai grass pasture with eucalyptus trees spaced 6 × 2m in summer and winter Light interception was the criteria for start grazing period and the height pasture was fixed in 20 cm as the residual. It was evaluated the grazing activities: feeding (FE), lying ruminating (LR), standing ruminating (SR), lying (LY), standing still (SS), searching for food (SF), and other activities (OT), body temperature (BT), respiratory frequency (RF), heart rate (HR). A sward stick and a 0.25m2 quadrat were used for measuring pasture height and density, in order to estimate the kg of DM/ha and the samples were split in green and dead material to assess the green dry matter yield (GY), and dead material dry matter yield (DY). Data were submitted to analysis of variance and F test at 5% significance, using the MIXED procedure of the statistical package SAS, and the treatments’ means were compared using Tukey test at 5% significance. Animals in IS stayed more time on LY, SS and having OA than animals in US and MS, for both seasons Also, they presented lesser HB, BT and RF than US during summer. In the winter, only BT was different for IS. Thus, IS had lesser DMY and GY, showing the Massai grass less tolerant to shading on both seasons. Because of the greater availability of shade, the silvopastoral system improved the state of welfare of the lambs, shown by the greatest time spent on ruminating. On the other hand, it altered the forage mass of the Massai grass.